Studi Literatur: Akupresur Titik P6 dalam Mencegah dan Mengurangi Mual dan Muntah Postoperasi - Harmiati Harmiati; Andi Masyitha Irwan; Elly Lilianty Sjattar (Politeknik Kesehatan Kemenkes Mamuju, 2018)
Postoperative nausea and vomiting are defined as nausea and vomiting occurring within 24 hours after surgery and is one of the complications of general anesthesia and neuroaxial anesthesia.This is still a major concern concern in patients undergoing surgery because it increases morbidity due to dehydration, electrolyte disturbance, aspiration, wound pain, pneumothorax, subcutaneous emphysema, esophageal rupture, which is resulting in delayed recovery, increased cost, and patient dissatisfaction. Although nausea and vomiting can be overcome by using antiemetics, its use is limited in clinical practice because it is related to the costs and side effects caused. Therefore, a special approach is necessary to improve patient comfort. Acupressure therapy point P6 is an effective method that can be used for the management of postoperative nausea and vomiting because in addition to easy to do, also cheap and have no side effects that can harm patients. To now P6 acupressure therapy in preventing and treating postoperative nausea vomiting. The method used in this study is review of articles fromelectronic journals database that have been published through Pubmed, Google Scholar and ProQuest. There are 44 articles identified and published from 2007-2017. The 7 articles out of 44 articles met the inclusion criteria. Some research results show the effectiveness of acupressure therapy in preventing an in reducing postoperative nausea and vomiting. Some approach can be implemented to reduce postoperative nausea and vomiting, but sometimes they have undesirable side effects. Acupressure therapy is one of the approach that could be recommended for reducing postoperative nausea and vomiting. Therefore the necessity for the application of acupressure therapy in the scope of nursing services.